Fatal Stevens-Johnson syndrome following urography with iopamidol in systemic lupus erythematosus. Issue 751 (May 1988) - Savill, J. S.; Barrie, R.; Ghosh, S.; Muhlemann, M.; Dawson, P.; Pusey, C. D.
Abstract : A 46 year old white woman with active systemic lupus erythematosus developed a skin rash 8 hours after intravenous urography with the non-ionic contrast medium iopamidol. Severe Stevens-Johnson syndrome with erythema multiforme, intrahepatic cholestasis, pulmonary infiltrates and acute renal failure ensued, leading to her death. Although non-ionic contrast media are generally less toxic than traditional ionic agents, their use in patients with immunological disease may be hazardous.